An Analysis of Students Ability to Answer Reading Questions with Higher Order Thinking Skills - Yuliman Laoli; Nursayani Maru'ao; Adieli Laoli; Riswan Zega (Universitas Muhammadiyah Enrekang, 2023)
The critical and creative thinking are crucial to be owned in this era. Thinking is one of the characteristics or characteristics of a person. Thinking is a mental activity experienced by a person when the person is faced with a situation or a problem that must be solved. Thinking is always related to the process of exploring ideas, forming various possibilities or alternatives, and being able to find solutions. The purpose of this research is to analyze what are the students' difficulties in answering HOTS questions and to investigate what are the factors that make students still make mistakes when answering reading questions with HOTS. From the results of the study explained that at the level of analysis students still have difficulties in translating or interpreting the meaning of the questions given, this is due to the lack of a list of vocabulary mastered by students. At the evaluation level students have difficulty processing information from the text given. At the level of creation, students have difficulty in making general conclusions so that students become constrained in creating new products. The second finding regarding the factors that make students still make mistakes in answering reading questions with HOTS is the lack of student study time, students' ability to learn English is still lacking, student mastery of HOTS material, and student learning situations. Researchers can conclude that the difficulties faced by students when answer HOTS questions and factors that make students still do mistakes in answer reading questions with HOTS are caused by a lack of understanding and ability of students to answer HOTS based questions.